Tom Boellstorff: Coming of Age of Second Life. An Anthropologist Explores of Virtual Human.: Princeton University Press, Princeton 2008, 316 s. - Beseda, Jan (Lidé města, 2009)
A review of the book by Tom Boellstorff.